2016
DOI: 10.3402/dfa.v7.27751
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise surgical approach to diabetic partial foot amputations with autogenous split thickness skin grafting

Abstract: In the surgical treatment of severe diabetic foot infections, substantial soft tissue loss often accompanies partial foot amputations. These sizeable soft tissue defects require extensive care with the goal of expedited closure to inhibit further infection and to provide resilient surfaces capable of withstanding long-term ambulation. Definitive wound closure management in the diabetic population is dependent on multiple factors and can have a major impact on the risk of future diabetic foot complications. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…The use of STSG has been echoed by other authors treating diabetic and ankle wounds. 33,34 Rose et al 35 reported a 69.1% rate of complete graft adherence in 94 patients undergoing non-ischemic chronic wound coverage, even on the plantar surface of the foot. In a 2-year retrospective study of a limited number of gTMAs receiving STSG, Holloway et al, 8 achieved 86% of complete wound healing in a median of 75 days.…”
Section: Discussionmentioning
confidence: 99%
“…The use of STSG has been echoed by other authors treating diabetic and ankle wounds. 33,34 Rose et al 35 reported a 69.1% rate of complete graft adherence in 94 patients undergoing non-ischemic chronic wound coverage, even on the plantar surface of the foot. In a 2-year retrospective study of a limited number of gTMAs receiving STSG, Holloway et al, 8 achieved 86% of complete wound healing in a median of 75 days.…”
Section: Discussionmentioning
confidence: 99%
“…Pada infeksi midfoot dan atau osteomielitis, intervensi bedah bertahap mungkin diperlukan untuk mencegah infeksi diikuti dengan rekonstruksi definitif. 16…”
Section: Artrodesis Kaki Tengahunclassified